Falah Mart Business Development Strategy as Foundation Supporter in Islamic Economic Perspective - Rauf, Abdul; Siradjuddin, Siradjuddin; Haddade, Wahid (Jurnal Ar-Ribh, 2024)
This research aims to determine the business development strategy of Falah Mart as a supporter of the Foundation and from an Islamic economic perspective. This research method is qualitative ex post facto focusing on seven research subjects through a purposive sampling method. Data was collected by conducting in-depth interviews and analyzed using the Miles and Huberman theory and SWOT analysis. The research results reveal that there are several strategies from internal and external factors that need to be developed through a combination SWOT Analysis matrix. Other strategies are product development, market development (price, promotion, distribution), business capital development, and human resource quality development. As for the Islamic economic perspective, Falah Mart applies the principles of honesty, friendliness, ta'awun (mutual help), responsibility, noble character, justice, cooperation, awareness of the welfare of life in this world and the hereafter.